2019
DOI: 10.1016/j.joca.2019.02.447
|View full text |Cite
|
Sign up to set email alerts
|

A culture engineering strategy to enhance mesenchymal stromal cells for treatment of osteoarthritis

Abstract: Purpose: Osteoarthritis (OA) is a debilitating disease associated with chronic inflammation, metabolic dysregulation, and progressive cartilage degradation in the joint. Mesenchymal stromal cells (MSCs) have been investigated as a promising therapy for the disease; however, insufficient in vivo potency and MSC donor variability can limit their efficacy. To address this, the Viswanathan lab has pioneered a proprietary culture engineering strategy to culture MSCs in 3D aggregates to augment their anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…MSCs are fundamentally responsive to subtle changes in their environment. MSCs respond to changes in atmospheric gases ( Lin et al, 2014 ; Gorgun et al, 2021 ; Roemeling-Van Rhijn et al, 2013 ; Ejtehadifar et al, 2015 ; Kang et al, 2019 ; von Bahr et al, 2019 ), temperature ( Stolzing et al, 2006 ; Kubrova et al, 2020 ; Shimoni et al, 2020 ), hydrostatic pressure ( Steward et al, 2012 ; Becquart et al, 2016 ; Pattappa et al, 2019 ) and aggregation ( Robb et al, 2019 ; Yuan et al, 2019 ; Burand et al, 2020 ; Xie et al, 2021 ). It is surprising then, that the steps and duration between dose preparation and delivery of MSC therapies are ill-defined and under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are fundamentally responsive to subtle changes in their environment. MSCs respond to changes in atmospheric gases ( Lin et al, 2014 ; Gorgun et al, 2021 ; Roemeling-Van Rhijn et al, 2013 ; Ejtehadifar et al, 2015 ; Kang et al, 2019 ; von Bahr et al, 2019 ), temperature ( Stolzing et al, 2006 ; Kubrova et al, 2020 ; Shimoni et al, 2020 ), hydrostatic pressure ( Steward et al, 2012 ; Becquart et al, 2016 ; Pattappa et al, 2019 ) and aggregation ( Robb et al, 2019 ; Yuan et al, 2019 ; Burand et al, 2020 ; Xie et al, 2021 ). It is surprising then, that the steps and duration between dose preparation and delivery of MSC therapies are ill-defined and under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the efficacy of MSCs for the treatment of OA, the Viswanathan lab pioneered an engineering strategy for culturing MSCs in 3D aggregates. The results showed that 3D MSCs reduced inflammation, fibrosis and cartilage degradation in both in vitro and in vivo models of OA compared to MSCs cultured using conventional 2D methods [ 138 ]. Furthermore, Brian et al isolated MSCs from the knee joint synovial fluid of three OA patients, epigenetically reprogrammed them, and then induced differentiation to establish a reprogrammed MSC (Re-MSC) line.…”
Section: Application Of Engineered Mscs In Autoimmune Diseasesmentioning
confidence: 99%
“…Increased complexity and non-standardized expansion protocols, alongside higher costs should be taken into consideration, when applying 3-D expansion techniques. However, reports about increased immunomodulatory and chondrogenic potential of MSCs, cultured in 3-D compared to conventional 2-D cultures, point towards promising technical developments in the field of tissue engineering for OA treatment [ 61 , 62 ]. The stromal vascular fraction (SVF) is a combination of ATMSCs, endothelial cells, growth factors, precursor cells, macrophages, t-regulatory cells, lymphocytes and others.…”
Section: Introductionmentioning
confidence: 99%